Cost–effectiveness of community-based treatment of severe acute malnutrition in children. (October 2010) - Bachmann, Max Oscar
Severe acute malnutrition affects 20 million children aged under 5 years old worldwide. Medical complications and death are common, but nutritional and medical treatment can result in good outcomes. Randomized trials of treatment after in-patient stabilization have shown community-based treatment to have similar outcomes to hospital-based treatment, at lower cost. Community-based ambulatory treatment, with in-patient care reserved for the most severe cases, is increasingly being implemented in Africa but has not been evaluated in randomized trials. Community-based treatment programs have shown favorable outcomes. Economic evaluations of community-based treatment have included cost analyses, cost and consequence analyses and decision analyses. Treatment costs have been consistently lower than for institution-based treatment. Costs of ambulatory community-based treatment of severe acute malnutrition have ranged between US$46 to $453 per child, depending on the type of care provided and the costing methods used. Recent studies have reported on costs and outcomes of similar large-scale African programs covering geographically defined populations, with ambulatory care for most children, and initial in-patient stabilization for the minority with most severe disease. In these studies the costs ranged from US$129 to $201 per child, and mortality rates ranged from 1.2 to 9.2%, depending on length of follow-up. A decision tree model based on such a program in Zambia estimated that community-based treatment of severe acute malnutrition in primary-care centers, with hospital access, cost US$203 per case treated, US$1760 per life saved, and US$53 per disability-adjusted life year gained, compared with no treatment. This latter cost per disability-adjusted life year gained suggests that community-based treatment of severe acute malnutrition is cost effective compared with other priority health interventions in low-income countries, and compared with such countries' national incomes.